Application status of XLPE insulated submarine cable used in offshore wind farm in China. Issue 13 (4th December 2017) - Zhang, Hongliang; Zhang, Jianmin; Duan, Lewis; Xie, Shuhong; Xue, Jianlin
Abstract : The application of cross‐linked polyethylene (XLPE)‐insulated submarine cable used in offshore wind farms in China is discussed. Different from onshore wind farms, the cable connects fans of offshore wind farms and transmits electric energy to booster stations installed under water. Therefore, to a certain extent, a mass of offshore wind farm construction in China promoted the development of XLPE‐insulated submarine cable. The aim of the application of XLPE‐insulated submarine cable for China's offshore wind power, first summarised the structural characteristics of three‐core AC submarine cable and introduced results of product structure improvement, production equipment upgrading and performance stability verification in the process of cable voltage levels of 35 to 110 and 220 kV. The product features and insulation structure design method of flexible DC submarine cable have been analysed. Finally, according to the trend of a large capacity and high seas construction for offshore wind farms, the application of XLPE‐insulated submarine cable will focus on wet‐type structure interconnecting submarine cable and high‐voltage flexible direct current submarine cable in the future.